2003
DOI: 10.4049/jimmunol.171.5.2354
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Mechanisms For Induction of Dendritic Cell Apoptosis in Response to IntactStreptococcus pneumoniae

Abstract: Apoptotic dendritic cells (DCs) are ineffective at inducing immunity. Thus, parameters that regulate DC viability during a primary infection will help to determine the outcome of the subsequent immune response. In this regard, pathogens have developed strategies to promote DC apoptosis to counterbalance the nascent primary immune response. We demonstrate, using cultured bone marrow-derived DCs, that Streptococcus pneumoniae can induce DC apoptosis through two distinct mechanisms: 1) a rapid, caspase-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 52 publications
6
67
1
Order By: Relevance
“…As demonstrated in another model, our experiments confirm that TLR2-dependent release of neurotoxins by microglia causes neuronal cell death (43). Additionally, initiation of TLR2-mediated and caspase-dependent cell death by pneumococcal cell wall has only been reported in TLR2-expressing cells such as endothelial cells or dendritic cells (41,44). Our finding of low TLR2-mRNA expression in resting astrocytes does not argue against an additional contribution of these cells in vivo because astrocytes have been shown to up-regulate TLR2 upon activation by bacterial compounds (45).…”
Section: Discussionsupporting
confidence: 65%
“…As demonstrated in another model, our experiments confirm that TLR2-dependent release of neurotoxins by microglia causes neuronal cell death (43). Additionally, initiation of TLR2-mediated and caspase-dependent cell death by pneumococcal cell wall has only been reported in TLR2-expressing cells such as endothelial cells or dendritic cells (41,44). Our finding of low TLR2-mRNA expression in resting astrocytes does not argue against an additional contribution of these cells in vivo because astrocytes have been shown to up-regulate TLR2 upon activation by bacterial compounds (45).…”
Section: Discussionsupporting
confidence: 65%
“…The present finding that IL-18 production induced by S. pneumoniae was dependent on TLR4 may account for the increased susceptibility to S. pneumoniae of mice that lack functional TLR4 (27). A previous report demonstrated that the interaction between PLY and TLR4 resulted in the induction of caspase-dependent host cell apoptosis in mice infected with S. pneumoniae (51), although several reports demonstrated that apoptosis-like cell death induced by S. pneumoniae or PLY in various types of cells is independent of caspases (6,10,12). In that report (51), it appeared that S. pneumoniae-induced apoptosis contributed to the host defense, because administration of the broad-spectrum caspase inhibitor z-VAD-fmk to mice increased the mortality rate after pneumococcal colonization in the nasopharynx.…”
Section: Discussionmentioning
confidence: 97%
“…Although induction of cell death is key to pathogenicity, the underlying mechanisms by which S. pneumoniae induces apoptosis (23)(24)(25) and necrosis (26) in host cells is not yet well understood. Although it is known that certain pneumococcal proteins elicit a potentially cytotoxic inflammatory response (4,27), here we asked whether S. pneumoniae or its secreted factors could directly generate DNA damage responses that could contribute to cell death. One such secreted factor could be hydrogen peroxide (H 2 O 2 ), produced by action of pyruvate oxidase (encoded by spxB) in S. pneumoniae (28), H 2 O 2 secreted by S. pneumoniae could potentially contribute to pneumococci-induced oxidative stress and elicit DNA damage response during infection.…”
Section: Significancementioning
confidence: 99%